ASSET-BASED COMMUNITY EMPOWERMENT THROUGH THE UTILIZATION OF FORMER VILLAGE TREASURY LAND IN URBAN SURABAYA - Tahmia Lestari; Eny Haryanti; Ika Devy Pramudiana; Amirul Mustofa (Journal Publicuho, 2025)
This study aims to analyse the form of community empowerment through the utilisation of Former Village Treasury Land (FVTL) in Tambak Wedi Village, Surabaya, focusing on the processes of participation, institutional challenges, and the impact on residents’ capabilities and welfare. A descriptive qualitative approach was employed, utilising in-depth interviews, participatory observation, and documentation as data collection techniques. Informants included residents, village officials, community leaders, and academic partners. The findings reveal that the utilisation of FVTL has created initial opportunities for community empowerment; however, its implementation continues to face significant structural barriers. Community participation remains largely tokenistic and has not yet reached a substantive level of decision-making. Moreover, the absence of a formal management institution has led to uncoordinated land use. Residents’ motivation fluctuates due to a lack of social incentives and the unequal distribution of benefits. Although individual skills have improved, these capabilities have not yet evolved into collective capacity. Coordination among stakeholders remains informal and lacks integration within a sustainable collaborative framework. This study underscores the importance of active community engagement throughout all stages of the program, the establishment of legally recognised local institutions, the provision of social incentives, and the formation of cross-sectoral collaborative forums to enhance program sustainability. The findings support the relevance of participation theory, the Asset-Based Community Development (ABCD) approach, and capability theory in the practice of local asset-based community empowerment.